Clinical and hematological profile of newborns delivered to mothers with pregnancy induced hypertension: a tertiary centre study - Mishra, Neerja; Arya, Arun Kumar; Lal, Pavika; Midha, Tanu; Verma, Neelima (International Journal of Contemporary Pediatrics, 2024)
Background: Pregnancy induced hypertension in women is a major cause of pregnancy related maternal, fetal, and neonatal morbidities and mortalities. Aim was to compare the clinical and hematological profile of newborns of mothers with and without pregnancy induced hypertension. Methods: This hospital-based case control study was conducted in Lala Lajpat Rai Hospital, Kanpur. Clinical and hematological profile of newborns of mothers with or without PIH were compared. Results: The low gestational age (35.44±2.89 weeks), low birth weight, thrombocytopenia (1.31±0.65 lakhs/mm3), absolute neutropenia (7.71×103±5.24×103cells/mm3) and deranged coagulation profile in newborns was found to have significant association with PIH in their mothers (p<0.05). Conclusions: This study concluded that newborns of hypertensive mothers carry a risk for prematurity, small for gestational age, infection and bleeding in early neonatal life.